Pemaknaan Klausula Menghadap Dalam Pelaksanaan Verlidjen Akta Notaril Melalui Media TeleKonfrensi di Era Digitalisasi - Abelia Lovena Sae; Dewati Candraningtyastuti (Faculty of Law, University of Jember, Indonesia, 2024)
Today's life cannot be separated from the development of science and technology such as the duties and roles of Notaries that require renewal to keep up with the times. Until now, the UUJN which has been in effect for approximately 10 years has not changed its contents. One thing that has not been regulated until now in the UUJN is regarding cyber notary. Therefore, the purpose of this writing is to analyze the interpretation of the